ANALISIS RANTAI NILAI EKONOMI PRODUK KERAJINAN LOKAL SEBAGAI PENUNJANG PARIWISATA DI KAWASAN NUSA DUA - Putu Ratna Windusara Putri; I Made Sujana; Ni Luh Wulani Parwati; Anak Agung Istri Setiari Jmh (Yayasan Nusantara Hasana Berdikari, 2024)
The development of the tourism sector in the Nusa Dua area has created significant economic opportunities for local handicraft businesses. However, the economic contribution of handicraft products to the tourism industry still faces several challenges, particularly regarding the unequal distribution of added value along the production chain. This study aims to analyze the economic value chain of local handicraft products as a supporting component of tourism in the Nusa Dua area. The research employed a qualitative descriptive approach using value chain analysis covering raw material procurement, production, distribution, marketing, and tourist consumption stages. Data were collected through observation, in-depth interviews, and documentation studies involving handicraft producers, souvenir traders, and tourism destination managers. The findings reveal that the highest added value is generated during marketing and direct sales to tourists, while artisans as primary producers receive relatively low profit margins. Product quality, design innovation, market accessibility, and digital technology utilization are identified as key determinants of economic value enhancement. The study recommends strengthening collaboration among government agencies, tourism industry stakeholders, and local artisans to establish a more inclusive and sustainable value chain.